2001
DOI: 10.1016/s0736-0266(00)00024-3
|View full text |Cite
|
Sign up to set email alerts
|

Both retinoic acid and 1,25(OH)2 vitamin D3 inhibit thyroid hormone‐induced terminal differentiaton of growth plate chondrocytes

Abstract: Thyroid hormone has been known for over 50 years to be a potent regulator of skeletal maturation at the growth plate. The receptor for thyroid hormone has been discovered to be a member of the nuclear hormone receptor superfamily. Retinoic acid and 1,25(OH)? vitamin D3. whose receptors also belong to this nuclear hormone receptor family, have been implicated in the control of chondrocyte proliferation and differentiation at the growth plate. Recent studies demonstrate that the receptors for thyroid hormone, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…To examine the regulatory pathways involved in MMP expression and activity in chicken and turkey growth plate, we examined two pathways that are known to induce MMPs; retinoic acid (RA), which is a differentiation factor in chon- drocytes (3,61) and an inducer of vascular invasion and premature fusion of the epiphyseal plate (12), and PMA, which is a protein kinase C activator that has been shown to induce transcription of most MMP genes (4).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the regulatory pathways involved in MMP expression and activity in chicken and turkey growth plate, we examined two pathways that are known to induce MMPs; retinoic acid (RA), which is a differentiation factor in chon- drocytes (3,61) and an inducer of vascular invasion and premature fusion of the epiphyseal plate (12), and PMA, which is a protein kinase C activator that has been shown to induce transcription of most MMP genes (4).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that this pellet culture system allows cells to terminally differentiate into hypertrophic chondrocytes that express high levels of alkaline phosphatase and type X collagen [39]. We used our custom-designed loading system to apply an intermittent hydrostatic compression force on these cell pellets, which resulted a markedly increased Ihh expression.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone exerts direct effects on chondrocytes [11][12][13][14] and is necessary for normal chondrocyte development [15] and endochondral ossification of the growth plate [16]. Children with hypothyroidism have reduced thickness of the growth plate of long bones, disorganization of the normal cartilage columns of the growth plate, and impaired differentiation of growth plate chondrocytes into hypertrophic cells resulting in growth retardation [15].…”
Section: Thyroid Hormone and Skeletal Growth And Maturationmentioning
confidence: 99%